148k views
2 votes
Solve for x. 2x-19 and x-6

Solve for x. 2x-19 and x-6-example-1
User Pjh
by
5.5k points

2 Answers

5 votes

Answer:

x = 13

Explanation:

NK = 23 and NK = (x - 6) + 9 + (2x - 19) = (x + 2x) + (-6 + 9 - 19) = 3x - 16

The equation

3x - 16 = 23 add 16 to both sides

3x = 39 divide both sides by 3

x = 13

User Chy
by
5.8k points
4 votes

Answer:

x=13

Explanation:

we have from the statement:

23 = (x-6)+9+(2x-19)

23 = x+3+2x-19

23 = 3x -16

23+16 = 3x

39 = 3x

x=39/3

x=13

User Dunc
by
6.4k points